New organic FET-like photoactive device, experiments and DFT modeling - Kratochvilová, I; Nesprek, S; Sebera, J; Zális, S; Pavelka, M; Wang, G; Sworakowski, J (The European physical journal. E, Soft matter, 2008)
We present the possible construction of an organic FET-like photoactive device in which source-drain current through a phthalocyanine ( H(2)Pc film is affected by a photo-induced dipolar field in a photoactive "gate" electrode. The influence of the dipolar electric field on charge transfer between H(2)Pc molecules is modeled by DFT quantum-chemical calculations on H(2)Pc dimers and tetramers.